CASO EICHMANN Y SUS EFECTOS CORRUPTORES EN LOS SISTEMAS GUBERNAMENTALES Y SOCIALES: UNA DISCUCIÓN INDISPENSABLE EN EL DERECHO PENAL - Vázquez Varela, Froylán Francisco (2021)
Adolf Eichmann was a general of the Nazi army who was tried for crimes in the Jewish genocide and condemned by the international community, however, the Arendtin theories on the banality of evil and on active life, Consider that in an organic way individuals construct moral rules within society, which in its turn does the same with individuals, but sometimes the social context can be the cause of lack of moral judgement in the individuals who commit felony. For criminal law this issue is of paramount relevance, given that, based of these theories, the excuse of liability for the crime can be raised in the event that subjects with criminal conduct have such a distortion of reality in that they do not give moral character to the laws or the orders of government systems. Therefore, this research conducts a philosophical-legal study on the problem of evil, where we reconsider the position of Arendt and Bauman to discuss the the posibility of adaptating criminal laws to contemplate the effect of the banality of evil or moral blindness in sentences.